Family Protection Policy in the UAE: A Descriptive Analytical Study - Albahri, Ghanima; Al-Othman, Hussain (Al-Adab Journal, 2024)
This research aimed at identifying the main axes and components of family protection policy in the UAE, in addition to examining the existence and availability of needed laws and services to protect family members from all forms of violence. The study used the descriptive method, where the researchers accessed the available data related to family protection policy in the UAE to conduct an intensive review of national legislations, laws, services, and programs related to the policy. Results showed that the policy consisted of five axes which are laws and regulations, protection and intervention mechanisms, increasing competencies, research and statistics, besides the prevention and community awareness axis. It was also found that the UAE government is highly committed to eliminating family violence through issuing several legislations and laws related to family rights and dedicating decent resources to support the provision of comprehensive protection, intervention and prevention services. However, the research showed that several improvements are needed in the areas of governance, law enforcement, accessibility, networking and effective participation from all the stakeholders. several corrective measures were proposed by the researchers to improve family protection policy in the country, the most prominent of which is the establishment of the Supreme Family Council in the country to exercise the supervisory and oversight role over all policies and services related to the family, as well as strengthening the awareness and preventive programs and conducting further quantitative and qualitative research, in addition to ensuring the activation of all legislations and regulations related to family protection.